Analysis of Datura stramonium Linn. biodiesel by gas chromatography - mass spectrometry (gc-ms) and influence of fatty acid composition on the fuel related characteristics - Koria, Litty; Nithya, G (Journal of Phytology, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Biodiesel is a mixture of fatty acid alkyl esters obtained by the reaction of triglycerides of vegetable or animal origin with alcohol in the presence of a catalyst. The fatty acid profile influences the overall properties of the biodiesel. The properties of individual fatty acid depend on the occurrence of double bonds, fatty acid chain length and branching. Better understanding of the fatty acid composition and correlating the fuel properties is of utmost importance in improving the optimal performance. In the present study, Datura stramonium biodiesel is analyzed for its fatty composition using Gas chromatography assisted with mass spectrometry. The influence of fatty acids of the fuel related properties is discussed.Â